Improvement of Transmission Line Matrix Method Algorithm Frequency Response Based on Modification of Cell Impedance - Rajabi , M.; Komjani, N. (Applied Computational Electromagnetics Society Journal (ACES), 2022)
In this paper, an accurate and numerically robust singularity correction technique for the transmission line matrix method (TLM) algorithm is proposed. The impedance of the adjacent cells to the singularity is corrected by a scalar correction factor, which amounts to a quasi-static correction of the electric and magnetic energy stored in the TLM cells at the singularity. The effectiveness of this method in accurate modeling of structures with metallic strips (sharp edges) and 90 degree edge corners has been clearly validated against published measurement and common TLM simulation data.